Different Doses of Intravenous Tissue-Type Plasminogen Activator for Acute Ischemic Stroke: A Network Meta-Analysis - Li, Bing-Hu; Wang, Jian-Hong; Wang, Han; Wang, Duo-Zi; Yang, Shu; Guo, Fu-Qiang; Yu, Neng-Wei (Frontiers in Neurology, 2022)
Background: To assess the efficacy and safety of different doses of intravenous tissue-type plasminogen activator (tPA) for acute ischemic stroke (AIS) by adopting a network meta-analysis (NMA). Methods: Studies comparing different doses of tPA in AIS were identified by retrieving electronic databases. NMAs of favorable functional outcome (mRS of 0 or 1) at 3 months after treatment (3M-FF), functional independence (mRS of 0, 1, or 2) at 3 months (3M-FI), symptomatic intracranial hemorrhage (sICH) and 3-months all-cause mortality (3M-M) were conducted. Probability-based ranking and surface under cumulative ranking (SUCRA) were performed to identify the best dose of tPA. Inconsistency was evaluated by node-splitting analysis and loop-specific approach. Publication bias was analyzed by funnel plots. Results: A total of fourteen studies were included in quantitative synthesis. The NMA results revealed no difference among low (＜0.7mg/kg), moderate (0.8mg/kg) and standard (0.9mg/kg) dose of tPA with regard to efficacy and safety. The SUCRAs of 3M-FF and 3M-FI showed that standard dose ranked the first, moderate dose ranked the second, and low dose ranked the third. The SUCRA of sICH showed that standard dose ranked the first (78.1%), low dose ranked the second (61.0%), moderate dose ranked the third (11.0%). The SUCRAs of 3-months mortality showed that standard dose ranked the first (73.2%), moderate dose ranked the second (40.8%), low dose ranked the third (36.1%). No significant inconsistency was shown by node-splitting analysis and no publication bias was shown in funnel plots. Conclusion: Lower dose tPA was comparable to standard dose with regard to efficacy and safety. Based on the SUCRAs results and AHA/ASA guidelines, standard dose was still the optimal selection for AIS.